AN OVERVIEW OF COMPUTER SOFTWARE FOR DEVELOPING SPATIAL THINKING SKILLS IN TEACHING GEOMETRY - Veli TOPTAŞ; Elif Tuğçe KARACA (International Journal of Eurasia Social Sciences, 2017)
The change and progress of technology affects every aspect of human life as well as it makes a serious contribution to the field of education. One of the most important contributions is undoubtedly the inclusion of computers into the teaching-learning process. In general, technology has offered the possibility of using different dynamic software for different purposes in mathematics education studies. Spesifically, the most popular software used in geometry objectives are GeoGebra, Cabri and so on. In addition to these software, Google SketchUp, which is both free and easy to use, has started to be used more and more in recent years. The importance of spatial skills which are considered necessary in the success of geometry and a part of mental ability is an important matter for many researchers. The computer can provide the environment to play with visual images, thus contributing to the development of spatial thinking. Dynamic geometry software such as GeoGebra, Cabri and Google SketchUp are especially found useful in situations where spatial thinking skills are desired to be improved, specifically in geometry. Therefore, in this study, the studies about the software that made contribution and improvement in spatial thought have been determined and analyzed. Findings obtained from the research can be expressed as these software have been found to provide positive contributions to spatial thinking.